Mai og Juni Maaned 1867. Agerdyrkningsberetning. (Fra Begyndelsen af Juli). - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Mai og Juni Maaned 1867. Agerdyrkningsberetning. (Fra Begyndelsen af Juli).